Mortality and life expectancy of Yokkaichi Asthma patients, Japan: Late effects of air pollution in 1960-70s - Suenaga Masami; Yokoyama Kazuhito; Guo Peng; Kida Hirotaka (BMC, 2008)
Abstract Background The incidence of chronic obstructive pulmonary disease (COPD) and bronchial asthma began increasing in early 1960s in the population of Yokkaichi-city (Mie Prefecture, Japan). The cause of the disease was sulfur oxide air pollution, and it is known as Yokkaichi Asthma. The pollution markedly decreased by the end of 1970s; no new cases have been reported since 1988. This study aimed at examining the late effects of air pollution on the health of Yokkaichi Asthma patients. Methods Mortality rate and life expectancy of patients, registered between 1965 and 1988, were investigated from 1975 through 2000. Results Mortality rates for COPD and asthma in patients from Yokkaichi-city were significantly higher than in the whole population of Mie Prefecture. For all ages (except for males between 80 and 84 years in 1985), the life expectancy of both males and females were significantly reduced in patients from Yokkaichi-city as compared with the whole population of Mie Prefecture. The potential gains in life expectancy excluding the mortality for respiratory diseases including COPD and asthma were larger for all ages in patients from Yokkaichi-city. Conclusion Mortality and life expectancy were adversely affected in patients from Yokkaichi-city, despite the fact that the air pollution problem has been already solved.